Peran Strategis Ahmadiyah dalam Pendidikan dan Dakwah di Dunia Barat Modern - Andy, Andy; Rakhmat, Rakhmat (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2024)
This research examines the strategic role of Ahmadiyah in education and da'wah in the modern Western world. The main issue addressed is how Ahmadiyah, often facing social and theological challenges, plays a significant role in promoting moderate and peaceful Islam in the West. The study aims to fill the gap in academic literature, which has rarely discussed Ahmadiyah's role in education and dawah. Using a library research approach, data were collected from relevant books, journals, and scientific articles. The research findings show that Ahmadiyah has established several educational institutions in Western countries, such as the UK and Canada, and uses modern media like MTA International to spread its message. Ahmadiyah also promotes interfaith dialogue and peaceful coexistence in pluralistic societies. The Tahrik Jadid movement, initiated by the second Khalifah, Mirza Bashiruddin Mahmud Ahmad, supports the construction of mosques and global education programs. In conclusion, Ahmadiyah has played an important role in strengthening the image of Islam as a peaceful religion in the West despite various challenges.